Practices and approaches of corporate citizenship by Public Relations (PR) department at Nestle Zimbabwe to enhance corporate reputation from 2010 to 2013 - Masuku, Caven; Shava, Tatenda (International Journal of Innovative and Applied Research, 2014)
This article seeks to assess the practice and approaches of Corporate Citizenship (CC) by the PR department at Nestle Zimbabwe to enhance corporate reputation from 2010 to 2013. It looks at how Nestle Zimbabwe has managed to boost its corporate reputation through CC and how they influence people’s decision making process through their help mechanisms. The study would be guided by Carroll’s (1991) model, two-way symmetrical model and the stakeholder’s salience model. Furthermore, the study applies triangulation through the use of both qualitative and quantitative research methods to obtain information closer to reality and validity. Again the study uses interviews, questionnaires and observations as tools for data gathering. For data analysis the article used content analysis to analyse the Nestle Zimbabwe documents and written articles. This article assesses the practices and approaches of CC by PR department at Nestle Zimbabwe to enhance corporate reputation from 2010 to 2013.